2020
DOI: 10.1177/2325967120926145
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of Meniscal Repair With Platelet-Rich Plasma: A Systematic Review of Comparative Studies

Abstract: Background: The effect of platelet-rich plasma (PRP) augmentation for meniscal repair (MR) is unclear, as current evidence is limited to small, mostly nonrandomized studies. Purpose: To systematically review the literature to evaluate the efficacy and safety of MR with PRP augmentation. Study Design: Systematic review; Level of evidence, 3. Methods: A systematic review was performed by searching PubMed, the Cochrane Library, and Embase to identify studies (level of evidence 1-3) that compared the clinical effi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 54 publications
(195 reference statements)
3
20
0
Order By: Relevance
“…Nevertheless, the low number of recently published studies underlines that the field of meniscal-repair augmentation is still in its infancy and is experiencing a rapid development. In fact, to date, results are still very controversial, and 2 recent systematic reviews concluded that patients undergoing meniscal repair with PRP augmentation experience clinical outcomes similar to those of conventional meniscal repair 4 and that the available evidence is insufficient to support the efficacy of PRP augmentation. 25 In particular, the second of these reviews 25 was a study that did not report failure rates and was therefore not included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the low number of recently published studies underlines that the field of meniscal-repair augmentation is still in its infancy and is experiencing a rapid development. In fact, to date, results are still very controversial, and 2 recent systematic reviews concluded that patients undergoing meniscal repair with PRP augmentation experience clinical outcomes similar to those of conventional meniscal repair 4 and that the available evidence is insufficient to support the efficacy of PRP augmentation. 25 In particular, the second of these reviews 25 was a study that did not report failure rates and was therefore not included in our meta-analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Most studies generally chose a follow-up period of 6 months, and only some studies had a follow-up period of more than 12 months. This may also be the reason for the difference between the results of this review and previous studies [41][42]. According to the evidence in this review, PRP enhances the meniscus, and no side effects were reported, which indicates that PRP is generally well tolerated.…”
Section: Discussionmentioning
confidence: 52%
“…105 A systematic review of 6 studies including 309 patients undergoing meniscal repair þ PRP augmentation versus 445 patients treated with repair alone reported repair failures in 17% of patients with PRP versus 22.1% of patients without PRP at a mean follow-up of 32.8 months. 105 Kaminski et al 106 reported significant improvements in patients receiving PRP þ repair versus repairs alone. Meniscal healing, evaluated on second-look arthroscopy or MRI, was present in 85% of repairs augmented with PRP versus 47% in the non-PRP group (P ¼ .048).…”
Section: Platelet-rich Plasmamentioning
confidence: 99%
“…The conflicting results in healing rates and PROs can be attributed largely to the differences in PRP formulation, with variable concentrations of platelets, leukocytes, and growth factors. 105…”
Section: Platelet-rich Plasmamentioning
confidence: 99%